6(2x+4)=8x-3

Simple and best practice solution for 6(2x+4)=8x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2x+4)=8x-3 equation:


Simplifying
6(2x + 4) = 8x + -3

Reorder the terms:
6(4 + 2x) = 8x + -3
(4 * 6 + 2x * 6) = 8x + -3
(24 + 12x) = 8x + -3

Reorder the terms:
24 + 12x = -3 + 8x

Solving
24 + 12x = -3 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
24 + 12x + -8x = -3 + 8x + -8x

Combine like terms: 12x + -8x = 4x
24 + 4x = -3 + 8x + -8x

Combine like terms: 8x + -8x = 0
24 + 4x = -3 + 0
24 + 4x = -3

Add '-24' to each side of the equation.
24 + -24 + 4x = -3 + -24

Combine like terms: 24 + -24 = 0
0 + 4x = -3 + -24
4x = -3 + -24

Combine like terms: -3 + -24 = -27
4x = -27

Divide each side by '4'.
x = -6.75

Simplifying
x = -6.75

See similar equations:

| r=6(2r+1) | | -2(3x-1)-4x=5x-(3x-6) | | -12n-(4n+5)=16-3n | | -10-bracket(-7)+2= | | 1/6×5= | | 3/2=3x-4/7 | | -8-(8)= | | 1/6×5 | | y-4x+110=0 | | x^2-9x+y^2=0 | | 7x^2-448= | | r=3(r+.5) | | 11/3×4/9 | | 6-9-(-6)= | | x-2y+74=0 | | 4/9×n=11/3 | | .8=.2+x-0.15 | | 3/100=n/660 | | x+5(x-5)=11 | | 3g+2g+5=0 | | Q^2+16q-15=0 | | 2(3+q)+q=3 | | 4-10-4-(-3)+3= | | an=1+(-1)n | | =2b*a | | 6(r+0.5)=r | | =2axb | | 5z+3=8z-4z | | h=-16t^2+132t+5 | | 0=32t^2+12t | | 3(r+0.5)=r | | 5(x+4)+2x=3(5x-4)-10x |

Equations solver categories